Cultivating recognition: a classic Grounded Theory of E-Learning providers working in East Africa - Tossy, Titus (University of Cape Town, 2024)
Thesis presented for the Degree of Doctor of Philosophy in the Department of Information Systems at the Faculty of Commerce University of Cape Town